2017
DOI: 10.1038/s41598-017-05818-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of the spermatheca identifies genes potentially involved in the long-term sperm storage of ant queens

Abstract: Females of social Hymenoptera only mate at the beginning of their adult lives and produce offspring until their death. In most ant species, queens live for over a decade, indicating that ant queens can store large numbers of spermatozoa throughout their long lives. To reveal the prolonged sperm storage mechanisms, we identified enriched genes in the sperm-storage organ (spermatheca) relative to those in body samples in Crematogaster osakensis queens using the RNA-sequencing method. The genes encoding antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(87 citation statements)
references
References 66 publications
(60 reference statements)
4
81
0
2
Order By: Relevance
“… *NS shows that the expression is not significantly different between samples (false discovery rate ≥ 0.01, Gotoh et al ., ). ERAP1, Endoplasmic reticulum aminopeptidase‐1; DHR, Disc‐large homologous regions.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“… *NS shows that the expression is not significantly different between samples (false discovery rate ≥ 0.01, Gotoh et al ., ). ERAP1, Endoplasmic reticulum aminopeptidase‐1; DHR, Disc‐large homologous regions.…”
Section: Resultsmentioning
confidence: 97%
“…Of 2292 contigs of the accessory glands that were highly expressed relative to the bodies in males, 559, 356 and 320 contigs were the same as contigs of the spermatheca in queens that were highly expressed relative to their bodies 1 week after mating, 1 year after mating, and both time frames, respectively (FDR < 0.01 and |log 2 fold change| ≥ 1; Fig. ), including comp71039_c3_seq1.m.351761 (thyrotropin‐releasing hormone‐degrading ectoenzyme‐like) and comp68199_c1_seq1.m.135927 (angiotensin‐converting enzyme, Tables and Supporting Information Table S1; Gotoh et al ., ). Whole‐mount in situ hybridization analyses revealed that comp71039_c3_seq1.m.351761 (thyrotropin‐releasing hormone‐degrading ectoenzyme‐like) was expressed not only in the accessory glands but also strongly expressed in the seminal vesicles of males (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Because queens are long lived but mate shortly after emergence from the pupae, the longterm storage of viable sperm in the queen's specialized organ (spermatheca) is another conundrum that is only now being investigated. Recent comparative transcriptomic analysis of spermatheca in virgin and mated Crematogaster queens identified a number of differentially expressed genes including some associated with antioxidizing function [45 ].…”
Section: Investigating Intraspecific Variation In Lifespanmentioning
confidence: 99%